Natural Dye of Beetroot: An Agent for Spectrophotometric Determination of Atenolol in the Pharmaceutical Formulations - Tahir, Tara F.; Aziz, Kurdistan F.; Kokhasmail , Dashne M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
In this study, a simple and indirect spectrophotometric method for the quantification of atenolol in pharmaceutical formulations, utilizing a natural food dye extracted from red beet root, is presented. The process involves the oxidation of atenolol in a 1 mol/LHCl acidic medium, using an excess of potassium persulfate. Subsequently, the resulting tablet solution is employed to fade the red beetroot dye, and the solution is measured spectrophotometrically. The optimized reaction conditions consist of a 16 µg/mL atenolol solution, 2.1 mL (100 µg/mL) of potassium persulfate, and 5 mL (100 µg/mL) of red beetroot dye. Spectrophotometric measurements were performed at 535 nm, and the linear range for quantification was found to be 4–22 µg/mL (R2 = 0.9987). The method exhibited a limit of detection of 0.01 µg/mL. Notably, the proposed method was successfully applied to analyze various commercial brands of pharmaceutical formulations; yielding results consistent with those obtained using the pharmacopeia method. This research offers a valuable and accessible technique for atenolol quantification, demonstrating potential significance in pharmaceutical analysis and quality control processes.